The floods in Thailand 2011 – A case study in the resilience of the food supply chain - Watcharathamrongkul, Kornthip (2012)
Recently, world population is increasing continuously while the resources are getting limited. Food which is the main factor for human existence needed to be secured in order to ensure the survival of residents in the nation. Thailand which is one of the food export countries plays the important role in the food supply chain to sustain the supply of food both within and outside the country. However, in 2011, Thailand was facing its severe massive flooding causing the adverse impacts across the country. The floods water had swamped a number of cultivated areas such as paddy fields and food crop fields as well as damaged the transportation infrastructures, resulting in the food supply chain disruption. From the severe situation, this study analyzes the influence of flooding over the resilience food supply chain using the devastating floods in Thailand 2011 as a case study. Moreover, rice is chosen to be reviewed in this thesis as the example of food supply chain due to its essential staple of Thai people and the most affected food crops from the floods. This research found that the current government’s resilient policies and strategic frameworks for the floods management which includes the prevention and mitigation, preparedness, response and recovery (long term) plans had been developed systematically in the view of food supply chain aspect. However, to enhance the resilient frameworks against future floods and to prevent the hunger in the country as well as to ensure the food supply chain continuity, the government agencies need to implement or take a strong action immediately when the floods strikes. Obviously, the suggestions to set up the emergency food stock, to develop the communication network and transportation infrastructures are useful to build on the strengths of country’s resilience plans so as to handle the floods risk and ensure the food security in the nation efficiently.